A COMPARATIVE ANALYSIS OF FLAX FIBRE FOR INDUSTRIAL APPLICATIONS - Gulhayo Mirboboeva; Navruza Isroilova; Malohat Rakhmonova (Western European Studies, 2024)
This article provides an in-depth evaluation of a newly developed linen fabric used in shirt production. The analysis covers its distinctive properties, focusing on the material's strengths and potential drawbacks. Furthermore, the article delves into the manufacturing processes involved, assesses the environmental sustainability of the fabric, and discusses its potential market prospects, including emerging trends and consumer demand
Keywords: linen; fibre; design; assortment